Antiviral activity of porphyrins and porphyrin-like compounds against tick-borne encephalitis virus: Blockage of the viral entry/fusion machinery by photosensitization-mediated destruction of the viral envelope - Holoubek, Jiří; Salát, Jiří; Kotouček, Jan; Kastl, Tomáš; Vancová, Marie; Huvarová, Ivana; Bednář, Petr; Bednářová, Klára; Růžek, Daniel; Renčiuk, Daniel; Eyer, Luděk (Antiviral research, 2024)
Tick-borne encephalitis virus (TBEV), the causative agent of tick-borne encephalitis (TBE), is a medically important flavivirus endemic to the European-Asian continent. Although more than 12,000 clinical cases are reported annually worldwide, there is no anti-TBEV therapy available to treat patients with TBE. Porphyrins are macrocyclic molecules consisting of a planar tetrapyrrolic ring that can coordinate a metal cation. In this study, we investigated the cytotoxicity and anti-TBEV activity of a large series of alkyl- or (het)aryl-substituted porphyrins, metalloporphyrins, and chlorins and characterized their molecular interactions with the viral envelope in detail. Our structure-activity relationship study showed that the tetrapyrrole ring is an essential structural element for anti-TBEV activity, but that the presence of different structurally distinct side chains with different lengths, charges, and rigidity or metal cation coordination can significantly alter the antiviral potency of porphyrin scaffolds. Porphyrins were demonstrated to interact with the TBEV lipid membrane and envelope protein E, disrupt the TBEV envelope and inhibit the TBEV entry/fusion machinery. The crucial mechanism of the anti-TBEV activity of porphyrins is based on photosensitization and the formation of highly reactive singlet oxygen. In addition to blocking viral entry and fusion, porphyrins were also observed to interact with RNA oligonucleotides derived from TBEV genomic RNA, indicating that these compounds could target multiple viral/cellular structures. Furthermore, immunization of mice with porphyrin-inactivated TBEV resulted in the formation of TBEV-neutralizing antibodies and protected the mice from TBEV infection. Porphyrins can thus be used to inactivate TBEV while retaining the immunogenic properties of the virus and could be useful for producing new inactivated TBEV vaccines.
Keywords: myši; Cations; protilátky virové; virový obal; Antibodies, Viral; RNA; Humans; Antiviral Agents; lidé; internalizace viru; Encephalitis, Tick-Borne; Viral Envelope; viry klíšťové encefalitidy; Encephalitis Viruses, Tick-Borne; Virus Internalization; kationty; Animals; Mice; zvířata; Porphyrins; klíšťová encefalitida; antivirové látky; porfyriny